The Effect of Various Sugars in Seaweed Drinks - FILDZAH NASUHA,; Faridah Kormin, (Enhanced Knowledge in Sciences and Technology, 2024)
Seaweed, widely acknowledged for its abundant nutritional composition. The research incorporates the infusion of sustainably sourced seaweed extracts from Muar, with an emphasis on preserving the natural flavours, colours, and health-enhancing compounds. the various sugar used were “gula apong”, “gula melaka”, rock sugar and monk fruit. 18 formulations were generated using Mixture Design in Design Expert (Stat-Ease, Inc., Trial Version 13). Physicochemical properties such as pH and total soluble solid (brix) along with sensory acceptance were evaluated. The sensory test indicated that the panelists accepted all 18 seaweed drink samples with sensory scores of 5 to 7. The pH for the samples was standardized to 3.60. The nutrient analysis demonstrated that sample 12 seaweed drinks were claimed as “free fat” and “low of sodium”. In short, seaweed drinks sample 12 was a new ready-to-serve beverage with highly acceptable sensory, physicochemical, and nutrient composition yet the total sugars content must be reduced.